Stress Doppler echocardiography for early detection of systemic sclerosis-associated pulmonary arterial hypertension - Nagel, Christian; Benjamin, Nicola; Blank, Norbert; Fischer, Christine; Lorenz, Hanns-Martin; Grünig, Ekkehard; Egenlauf, Benjamin (Arthritis Research & Therapy, 2015)
In patients with systemic sclerosis (SSc), associated pulmonary arterial hypertension (SSc-APAH) is the leading cause of death. The objective of this prospective screening study was to analyse sensitivity and specificity of stress Doppler echocardiography (SDE) in detecting pulmonary hypertension (PH). Pulmonary artery pressures and further parameters of PH were assessed by echocardiography and right heart catheterisation (RHC) at rest and during exercise in patients with SSc. Investigators of RHC were blinded to the results of non-invasive measurements. Of 76 patients with SSc (64 were female and mean age was 58±14 years), 22 (29 %) had manifest PH confirmed by RHC: four had concomitant left heart diseases, three had lung diseases, and 15 had SSc-APAH. Echocardiography at rest missed PH diagnosis in five of 22 patients with PH when a cutoff value for systolic pulmonary arterial pressure (PASP) was more than 40 mm Hg at rest. The sensitivity of echocardiography at rest was 72.7 % (95 % confidence interval (CI) 0.52-0.88), and specificity was 88.2 % (95 % CI 0.78-0.95). When a cutoff value for PASP was more than 45 mm Hg during low-dose exercise, SDE missed PH diagnosis in one of the 22 patients with PH and improved sensitivity to 95.2 % (95 % CI 0.81-1.0) but reduced specificity to 84.9 % (95 % CI 0.74-0.93). Reduction of specificity was partly due to concomitant left heart disease. The results of this prospective cross-sectional study using RHC as gold standard in all patients showed that SDE markedly improved sensitivity in detecting manifest PH to 95.2 % compared with 72.7 % using echocardiography at rest only. Thus, for PH screening in patients with SSc, echocardiography should be performed at rest and during exercise. ClinicalTrials.gov NCT01387035 . Registered 29 June 2011.
Gesehen am 10.08.2020